A dynamic matrix potentiates mesenchymal stromal cell paracrine function via an effective mechanical dose. (29th July 2020) - Lin, Chuanchuan; Xu, Kun; He, Ye; Tao, Bailong; Yuan, Zhang; Li, Ke; Li, Xuemin; Xia, Zengzilu; Cai, Kaiyong
Abstract : Compared to static conditions, MSCs in a dynamic matrix possess higher paracrine function as a result of collecting a mechanical dose through a cytoskeleton-YAP system. Abstract : The paracrine function of mesenchymal stromal cells (MSCs) contributes a lot to tissue development, and it is regulated by various physical factors. Moreover, the extracellular matrix (ECM) of MSCs is dynamic, and its remodeling is always occurring. In particular, stiffness changes are prevalent. Accordingly, ECM stiffness changes may affect the paracrine function of MSCs, which has not been investigated much. In this study, for the first time, alginate hydrogels with different stiffening times were used to assess the influence of dynamic ECM stiffness changes on the paracrine function of MSCs. It was found that a stiffer matrix (14.72 ± 1.44 kPa) under static conditions without any additional treatment could significantly potentiate the paracrine function of MSCs compared to a soft matrix (2.44 ± 0.23 kPa). Furthermore, this promotion was regulated by the activation of Yes-associated protein (YAP), which was caused by the polymerization of F-actin. Intriguingly, in a dynamic system, the MSC-encapsulating matrix that stiffened on the third day had stronger YAP activation than the Static-Stiff matrix. However, this activation was weakened when MSCs were cultured in a matrix that stiffened on the fifth day. The results show that an increase in ECM mechanical dosing levels would promote the paracrine function of MSCs. Moreover, an effective mechanical dose that can influence the paracrine function of MSCs indeed exists.